Understanding the Impact of Urinary Incontinence in Persons with Dementia: Development of an Interdisciplinary Service Model - Patrick Juliebø-Jones; Elizabeth Coulthard; Elizabeth Mallam; Hilary Archer; Marcus J. Drake (Advances in Urology)
Introduction. Prevalence of urinary symptoms such as incontinence (UI) in patients with dementia is estimated to exceed 50%. The resultant psychological and socio-economic burden can be substantial. Our aim was to develop a dedicated urology service within a cognitive impairment clinic in order to treat and better understand the bothersome urinary symptoms suffered by persons with dementia. Methods. Patients attending this clinic were invited to be assessed and interviewed by urologist, together with their family and/or carer. In addition, formal history, examination and relevant investigations, themes of importance such as quality of life, and select question items were drawn from validated questionnaires. Multidisciplinary team (MDT) meeting was carried out on the same day. Outcomes of the first 75 patients with UI and dementia have been reported. Results. Average age was 70 years (range 58–98). Majority of persons had a diagnosis of Alzheimer’s disease (n = 43, 57%). Average score for how much urine leakage interferes with everyday life was 7.7/10 (range 2–10). 58.7% (n = 44) revealed some degree of sleep disturbance due to UI. 83% (n = 62) stated daily activities were limited due to UI. Two-thirds of persons with dementia (n = 50) stated their bladder problem makes them feel anxious. 88% (n = 67) felt the topic was socially embarrassing. All carers stated that the person’s continence issues affect the care they provide. Less than one-third of carers (30.7%, n = 23) were aware of or had been in contact with any bladder and bowel community service. More than half of the carers (n = 46, 65%) were concerned incontinence may be a principal reason for future nursing home admission. Conclusion. UI can be distressing for persons with dementia. Care partners were concerned about loss of independence and early nursing home admission. Awareness of bladder and bowel services should be increased.